Penerapan Model Pembelajaran Think Talk Write Menggunakan Media Power Point untuk Meningkatkan Komunikasi Siswa - Fatma Yuniati; Sri Haryanto; Firdaus Firdaus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Abstract: This study aims to determine how the level of communication skills is seen from the group of students' initial understanding and the level of students' final understanding. Is there a difference, and how much is the increase in students' communication results after applying the Think Talk Write model using PowerPoint media? This type of quantitative research with quasi-experiments utilizing a control group design. The population in the study was class VIII A as the control class and class VIII B as the experimental class, each of which consisted of 20 students. Data collection was obtained using the method of documentation, testing, and communication observation. The results showed that the application of the TTW Learning Model (Think Talk Write) using PowerPoint media to improve students' communication skills for the initial level of student communication results was included in the low category, with an average of 48.70 for the control class and 48.70 for the experimental type. The story of student communication is obtained from the pre-test scores. The students' final communication results increased after treatment, averaging 72.75 for the control class and 90.30 for the experimental type. The students' last communication level was obtained from the post-test scores. In conclusion, there are differences in improving communication results using the Think Talk Write (TTW) learning model using PowerPoint (PPT) media to improve student communication. Keywords: Student Communication, PowerPoint, Think Talk Write